2017
DOI: 10.1542/peds.2017-0471
|View full text |Cite
|
Sign up to set email alerts
|

Allergy Testing in Children With Low-Risk Penicillin Allergy Symptoms

Abstract: All children categorized as low-risk by our penicillin allergy questionnaire were found to have negative results for true penicillin allergy. The utilization of this questionnaire in the pediatric ED may facilitate increased use of first-line penicillin antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 15 publications
1
83
1
2
Order By: Relevance
“…In our prospective study, only 5.2% of all children reporting a DHR to a BL had a proven hypersensitivity to the suspected BL, which is a lower percentage if compared with previous reports . This might be due to the characteristics of our pediatric population, with >90% of patients having a non‐immediate initial reaction, which rarely results to be true DHRs.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…In our prospective study, only 5.2% of all children reporting a DHR to a BL had a proven hypersensitivity to the suspected BL, which is a lower percentage if compared with previous reports . This might be due to the characteristics of our pediatric population, with >90% of patients having a non‐immediate initial reaction, which rarely results to be true DHRs.…”
Section: Resultscontrasting
confidence: 69%
“…In children treated with BLs, skin eruptions, mostly described as maculopapular or urticarial, are frequently assumed to be a DHR, although most of these eruptions are not allergic, with viral infections being often considered as the major differential diagnosis. 3,16 It is therefore very important to complete an allergy workup in patients reporting a history of BL DHR. 16 Older EAACI/ENDA guidelines do not differentiate between children and adults and advise to perform several ST (both SPTs and IDTs) before running a DPT.…”
Section: Con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97][98] At present, direct ingestion has been done in carefully selected cohorts, predominantly healthy children or healthy adults, whose historical symptoms were at lower risk of true penicillin allergy. 39,43,95,99 (Table 2) Direct provocation of a penicillin-labeled patient without preceding skin testing appears to be an important tool in the de-labeling toolkit, as tolerance demonstrates the absence of immediate hypersensitivity. This approach has been particularly relevant in children where the pretest risk of true anaphylaxis was very low.…”
Section: Patients With a Low-risk History Or A History Inconsistent Wmentioning
confidence: 99%
“…An evaluation conducted in a pediatric emergency department that involved 100 children with a history of penicillin allergy found that 100% (95% CI 96.4%-100%) of these children with low-risk symptoms had negative results for allergy testing (skin testing and drug provocation test). 37 Evaluation is especially useful if the reaction occurred more than 5 to 10 years ago, because there is a high rate of resolution for penicillin allergy. [38][39][40] For example, a retrospective study involving 740 patients with a history of β-lactam allergy found that 93% of these patients had a positive result for skin testing if the reaction was in the past year; this decreased to 22% of patients with a positive test result if they were evaluated 10 or more years after their clinical reaction.…”
Section: Penicillinmentioning
confidence: 99%